### Present Remotely

Send the link below via email or IM

CopyPresent to your audience

Start remote presentation- Invited audience members
**will follow you**as you navigate and present - People invited to a presentation
**do not need a Prezi account** - This link expires
**10 minutes**after you close the presentation - A maximum of
**30 users**can follow your presentation - Learn more about this feature in our knowledge base article

# recursive and explicit formulas

No description

by

Tweet## Arrin Smith

on 4 January 2013#### Transcript of recursive and explicit formulas

math project

recursive and explicit formulas recursive formulas an = an-1 + d arithmetic formula: you need to know the previous term to be able to determine the answer geometric formula: an = r(an-1) a1 = first term in the sequence

an = the nth term

an-1 = the term BEFORE the nth term

d = common difference (could be negative)

r = common ratio (could be fraction) arithmetic example:

-4, -6, -8, -10 recursive: an=an-1+d

an=an-1 -2

a(5)=(-10)-2

a(5)=-12

a(6)=(-12)-2

a(6)=-14

a(7)=(-14)-2

a(7)=-16 -4, -6, -8, -10, -12, -14, -16 geometric example: 25, 75, 225 recursive formula an=r(an-1) ratio term after over term before an=3(an-1) a(4)=3(225)

a(4)=675

a(5)=3(675)

a(5)=2025 25, 75, 225, 675, 2025 explicit based on the term number arithmetic formula: geometric formula: an = a1 + d(n – 1) an = a1(r^n-1) a1 = first term in the sequence

an = the nth term

an-1 = the term BEFORE the nth term

d = common difference (could be negative)

r = common ratio (could be fraction) arithmetic example explicit -4, -6, -8, -10 an= a1+d(n-1) an=-4-2(n-1) a(5)=-4-2(4)

a(5)=-4-8

a(5)=-12

a(6)=-4-2(5)

a(6)=-4-10

a(6)=-14 -4, -6, -8, -10, -12, -14 an = a1(r^n-1) geometric example explicit 25, 75, 225 an = 25(3^n-1)

a(4)=25(3^3)

a(4)=25(27)

a(4)=675

a(5)=25(3^4)

a(5)=25(81)

a(5)=2025 25, 75, 225, 675, 2025 Richard Bjorneby

Full transcriptrecursive and explicit formulas recursive formulas an = an-1 + d arithmetic formula: you need to know the previous term to be able to determine the answer geometric formula: an = r(an-1) a1 = first term in the sequence

an = the nth term

an-1 = the term BEFORE the nth term

d = common difference (could be negative)

r = common ratio (could be fraction) arithmetic example:

-4, -6, -8, -10 recursive: an=an-1+d

an=an-1 -2

a(5)=(-10)-2

a(5)=-12

a(6)=(-12)-2

a(6)=-14

a(7)=(-14)-2

a(7)=-16 -4, -6, -8, -10, -12, -14, -16 geometric example: 25, 75, 225 recursive formula an=r(an-1) ratio term after over term before an=3(an-1) a(4)=3(225)

a(4)=675

a(5)=3(675)

a(5)=2025 25, 75, 225, 675, 2025 explicit based on the term number arithmetic formula: geometric formula: an = a1 + d(n – 1) an = a1(r^n-1) a1 = first term in the sequence

an = the nth term

an-1 = the term BEFORE the nth term

d = common difference (could be negative)

r = common ratio (could be fraction) arithmetic example explicit -4, -6, -8, -10 an= a1+d(n-1) an=-4-2(n-1) a(5)=-4-2(4)

a(5)=-4-8

a(5)=-12

a(6)=-4-2(5)

a(6)=-4-10

a(6)=-14 -4, -6, -8, -10, -12, -14 an = a1(r^n-1) geometric example explicit 25, 75, 225 an = 25(3^n-1)

a(4)=25(3^3)

a(4)=25(27)

a(4)=675

a(5)=25(3^4)

a(5)=25(81)

a(5)=2025 25, 75, 225, 675, 2025 Richard Bjorneby